A methodology for the customization of hinged ankle-foot orthoses based on in vivo helical axis calculation with 3D printed rigid shells. (April 2021) - Ferraresi, Carlo; De Benedictis, Carlo; Bono, Loris; Del Gaudio, Federica; Ferrara, Laura; Masiello, Fabiana; Franco, Walter; Maffiodo, Daniela; Leardini, Alberto
This study aims to develop techniques for ankle joint kinematics analysis using motion capture based on stereophotogrammetry. The scope is to design marker attachments on the skin for a most reliable identification of the instantaneous helical axis, to be targeted for the fabrication of customized hinged ankle-foot orthoses. These attachments should limit the effects of the experimental artifacts, in particular the soft-tissue motion artifact, which affect largely the accuracy of any in vivo ankle kinematics analysis. Motion analyses were carried out on two healthy subjects wearing customized rigid shells that were designed through 3D scans of the subjects' lower limbs and fabricated by additive manufacturing. Starting from stereophotogrammetry data collected during walking and dorsi-plantarflexion motor tasks, the instantaneous and mean helical axes of ankle joint were calculated. The customized shells matched accurately the anatomy of the subjects and allowed for the definition of rigid marker clusters that improved the accuracy of in vivo kinematic analyses. The proposed methodology was able to differentiate between subjects and between the motor tasks analyzed. The observed position and dispersion of the axes were consistent with those reported in the literature. This methodology represents an effective tool for supporting the customization of hinged ankle-foot orthoses or other devices interacting with human joints functionality.